Pengaruh Pengetahuan, Produk dan Religiusitas Terhadap Minat Menabung dengan Variabel Moderating Persepsi - Alifah Dwi Novianti; Luqman Hakim (Jurnal Pendidikan Akuntansi (JPAK), 2021)
The Purpose of this study to analyze the knowledge of Islamic banking, bank products and religiosity towards saving interest in Islamic banks with perception as a moderating variable. This type of research is quantitative. Active students of Islamic economics study programs at three state universities in Surabaya as research sample numbered 100 students using the quota sampling technique. Data collection techniques with questionnaires. The results show there is an influence of Islamic banking knowledge on saving interest, there is an influence of bank products on saving interest, there is an influence of religiosity on saving interest, perception is not a moderating variable of sharia banking knowledge with saving interest, perception is not a moderating variable of bank products with saving interest, perception is a moderating variable of religiosity with saving interest.